Efficient nano-preparation, characterization, and biological evaluation of two Schiff base-derived complexes - Ali Qaid, Ahmed; Azzam , Sadeq Hamood; Al-Gaadb, Amani Ahmed; Alattab, Bushra Mohammed; Alarbagi, Fares Abdullah; Al-qadasy, Mohammed Kassem; Al-Arnoot, Saad Abdullah; Al-Maqtari, Maher Ali (Eclética Química, 2026)
This study aims to prepare a new Schiff base, 2-[(E)-[2-(2,4-dinitrophenyl)hydrazinylidene]methyl]-1H-pyrrole (NPHP), derived from 2,4-dinitrophenyl hydrazine and 1H-pyrrole-2-carbaldehyde with ratio 1:1. Additionally, two new complexes of this Schiff base were synthesized with transition metal ions, Ni(II) and Cu(II), with ligand to metal ratio 2:1. The complexes were characterized using molar conductivity, FT-IR, UV-Vis, 1HNMR, 13CNMR, XRD, and transmission electron microscopy. Physicochemical properties and spectral results indicate that the conductivity showed an electrolytic nature for these complexes, and the ligand acts as a bidentate chelating agent with octahedral geometry, as supported by FT-IR and UV-Vis analysis. The azomethine (CH=N) nitrogen and pyrrole nitrogen atoms were identified as the coordination sites. Pathogenic bacterial studies for the ligand and its new complexes, Ni(II) and Cu(II), were conducted against Escherichia coli, Staphylococcus aureus, and Pseudomonas aeruginosa. Based on chelation theory, the metal complexes exhibited higher biological activity than the free ligand, while the complex of Ni(II) was more effective than the complex of Cu(II). Notably, the Schiff base (NPHP) showed no activity against Escherichia coli.